2013
DOI: 10.1063/1.4776740
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced dielectric properties of BaTiO3/poly(vinylidene fluoride) nanocomposites for energy storage applications

Abstract: In this work, homogeneous ceramics-polymer nanocomposites consisting of surface treated BaTiO3 (BT) particles as fillers and poly(vinylidene fluoride) polymer as matrix have been prepared using a solution casting process. The nanocomposites exhibit enhanced dielectric permittivity and reduced loss tangent. The frequency and temperature dependencies of the dielectric permittivity and loss tangent of the nanocomposites suggest that the introduced BT phase and interface areas contribute to the improvement of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
106
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(114 citation statements)
references
References 46 publications
5
106
3
Order By: Relevance
“…The printed composite showed higher relative permittivity than has been previously reported with the same loading level, while the dielectric losses remain at the same level [8][9][10][11][12][13][14][15]. This is almost certainly due to the selection of the matrix material and the particle size, and the new fabrication technique including chemical solution processing with specific surfactant and printing which enabled a low agglomeration level and a more uniform distribution of the filler.…”
Section: Dielectric Propertiescontrasting
confidence: 39%
“…The printed composite showed higher relative permittivity than has been previously reported with the same loading level, while the dielectric losses remain at the same level [8][9][10][11][12][13][14][15]. This is almost certainly due to the selection of the matrix material and the particle size, and the new fabrication technique including chemical solution processing with specific surfactant and printing which enabled a low agglomeration level and a more uniform distribution of the filler.…”
Section: Dielectric Propertiescontrasting
confidence: 39%
“…[12] However, a high ceramic filler loading (beyond 50% vol) is required to considerably increase the dielectric constant. [13] Also, with the increase of filler loading, the mechanical characteristics of the nanocomposites suffer a decline. The last few years have seen a revival in the study of polymers reinforced by twodimensional fillers, especially graphene due to its exceptionally high modulus (Y ≈ 1 TPa) and strength (σ B ≈ 130 GPa).…”
Section: Introductionmentioning
confidence: 99%
“…Surface modification of the nanoparticle fillers produces a surface coating layer that increases the electric field strength at breakdown and lowers the dielectric loss [22]. Yu et al [23] reported that the addition of surface modified BaTiO 3 particles in poly(vinylidene fluoride) enhances the dielectric properties and reduces dielectric loss, even at high filler loading. Choudhury [11] stated that the addition of active hydroxyl -OH groups on the surface of the BaTiO 3 particles produces a more uniform dispersion of the nanoparticles in a polyetherimide matrix, thus increasing the low-frequency dielectric permittivity and decreasing dielectric loss.…”
Section: Introductionmentioning
confidence: 99%